PENGARUH LATIHAN RONDO TERHADAP PENINGKATAN KEMAMPUAN KONTROL BOLA PADA ATLET SEPAK BOLA CLUB GENERASI INSPIRATIF KARO TAHUN 2025 - Dio Valentino Bangun; Julius Boy Nesra Basgimata Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of rondo training on improving ball control skills in football athletes of Generasi Inspiratif Karo Club. This research uses a quasi-experimental method with one group pretest-posttest design. The subjects were 15 athletes selected using purposive sampling technique. The intervention was carried out for 1 month with a frequency of 3 meetings per week. Data collection uses a ball control test instrument with indicators of first touch, ball control under pressure, and passing accuracy. The results showed that the average pretest score was 9.00 (sufficient category) and the posttest average was 12.60 (good category), with an increase of 40%. Statistical analysis using Paired Sample t-Test obtained t-value = 14.52 and p-value = 0.000 (p < 0.05). Thus, it can be concluded that rondo training has a significant effect on improving ball control skills. This method is recommended as a routine training program for youth football athletes.